Effects of Study Skills Training on Achievement in Mathematics of Low Achieving Upper Basic Students in Plateau State, Nigeria - Israel, Justina Oluchi; Bahago, Beatrice Ahmedu (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
The study investigated the effects of study skills training on achievement in Mathematics of the low achieving Upper Basic Students in Jos East, Nigeria.  The purpose of the study was to find out whether study skills training improved the Upper Basic Students study habits and achievement in Mathematics.  Two research questions as well as two hypotheses were formulated to guide the study.  The study as well, adopted the Stimulus Response (SR) Theory of Edward Thorndike as its theoretical framework.  The population of the study comprised of all the Upper Basic Students 2 in Jos East Local Government Area of Plateau State, while the sample were 70 respondents (35 boys and 35 girls), who were assigned to the experimental and control groups.  The study adopted the pre-test post-test control group, experimental research design.  To further investigate on this, the study used two research instruments namely: the Study Skills Questionnaire (SSQ) and the Mathematics Achievement Test (MAT) to collect data.  The data collected were analysed using the mean, standard deviation and analysis of covariance (ANCOVA).  Findings from the study revealed that prior to intervention, the Upper Basic Students had low study skills and achievement in Mathematics, but improved in both areas after exposure to study skills training.  Based on this therefore, the research recommends among others that in order to enhance studentsâ€™ study skills and achievement in Mathematics, study skills training be introduced early in school years, so as to enable students develop effective study habits, and also, educational administrators of secondary schools should organize seminars and workshops for school teachers on training in study skills for maximum output in the subjects taught in schools. Keywords: Study skills, study skills training, Mathematics achievement in Mathematics, low achieving students.